Variations in Origin and Branching Pattern of Anterior Division of Internal Iliac Artery: a Cadaveric Study - Pradhan, Allin; Pradhan, Manish Man; Kharbuja, Rabita; Karki, Deepika; Dhungel, Shaligram (Journal of College of Medical Sciences-Nepal, 2022)
Introduction: Detailed knowledge of the branching pattern of internal iliac artery will be a guidance for ligating the artery and its branches during various pelvic surgeries. Hence, the main objective of this study was to know the branching pattern of internal iliac artery, based on the Adachis Classification along with the length and diameter of the arteries. Methods: The descriptive observational cross-sectional study was conducted at the Department of Human Anatomy of the Nepal medical college, examined over a period of 9 months from June 2021- February 2022 which included 30 internal iliac arteries and its branches of right and left sides from 15 embalmed male human cadavers. Results: In the study, branching pattern of internal iliac artery (IIA) was Type Ia in 19 (63.33%) and Type III in 11 (36.66%) of the cases while type I b, Type II a, Type II b, IV and V pattern were not observed. The total minimum and maximum lengths of both right and left trunk of internal iliac arteries were 1.33 cm and 3.42 cm respectively and average lengths with standard deviation were 2.61cm ± 0.66.The calculated P-value (0.002) showed that the differences between the lengths of IIA of both sides were statistically significant. The diameter and standard deviation of IIA and obturator artery were 6.35±1.31 and 2.47cm±0.67 respectively. The obturator artery was found to be originated from both anterior and posterior division of IIA accounting as 96.66% and 3.33% respectively. Conclusions: Pelvic surgeries may lead to hemorrhage if branching patterns of the IIA are incorrectly interpreted and thus endanger the patient’s life while ligating the artery during prostatectomy, hernioplasty. The current study explain the important aspects of the vascular anatomy of the IIA not only for anatomists and morphologists, but also for the radiologists, general and vascular surgeons. Key words: internal iliac artery; inferior gluteal artery; internal pudendal artery; obturator artery; variations.